Efficacy and safety of oral semaglutide with flexible dose adjustment versus sitagliptin in type 2 diabetes (PIONEER 7): a multicentre, open-label, randomised, phase 3a trial. Issue 7 (July 2019) - Pieber, Thomas R; Bode, Bruce; Mertens, Ann; Cho, Young Min; Christiansen, Erik; Hertz, Christin L; Wallenstein, Signe O R; Buse, John B; ,
Summary: Background: Oral semaglutide is the first oral formulation of a glucagon-like peptide-1 (GLP-1) receptor agonist developed for the treatment of type 2 diabetes. We aimed to compare the efficacy and safety of flexible dose adjustments of oral semaglutide with sitagliptin 100 mg. Methods: In this 52-week, multicentre, randomised, open-label, phase 3a trial, we recruited patients with type 2 diabetes from 81 sites in ten countries. Patients were eligible if they were aged 18 years or older (19 years or older in South Korea), had type 2 diabetes (diagnosed ≥90 days before screening), HbA1c of 7·5–9·5% (58–80 mmol/mol), and were inadequately controlled on stable daily doses of one or two oral glucose-lowering drugs (for 90 days or more before screening). Participants were randomly assigned (1:1) by use of an interactive web-response system, stratified by background glucose-lowering medication at screening, to oral semaglutide with flexible dose adjustments to 3, 7, or 14 mg once daily or sitagliptin 100 mg once daily. To approximate treatment individualisation in clinical practice, oral semaglutide dose could be adjusted on the basis of prespecified HbA1c and tolerability criteria. Two efficacy-related estimands were prespecified: treatment policy (regardless of treatment discontinuation or use of rescue medication) and trial product (on treatment and without use of rescue medication) for participants randomly assigned to treatment. The primary endpoint was achievement of HbA1c of less than 7% (53 mmol/mol) at week 52 and the confirmatory secondary efficacy endpoint was change in bodyweight from baseline to week 52. Safety was assessed in all participants who received at least one dose of study drug. This trial is registered with ClinicalTrials.gov, number NCT02849080, and European Clinical Trials Database, EudraCT number 2015-005593-38, and an open-label extension is ongoing. Findings: Between Sept 20, 2016, and Feb 7, 2017, of 804 patients assessed for eligibility, 504 were eligible and randomly assigned to oral semaglutide (n=253) or sitagliptin (n=251). Most participants were male (285 [57%] of 504) with a mean age of 57·4 years (SD 9·9). All participants were given at least one dose of their allocated study drug except for one participant in the sitagliptin group. From a mean baseline HbA1c of 8·3% (SD 0·6%; 67 mmol/mol [SD 6·4]), a greater proportion of participants achieved an HbA1c of less than 7% with oral semaglutide than did with sitagliptin (treatment policy estimand: 58% [134 of 230] vs 25% [60 of 238]; and trial product estimand: 63% [123 of 196] vs 28% [52 of 184]). The odds of achieving an HbA1c of less than 7% was significantly better with oral semaglutide than sitagliptin (treatment policy estimand: odds ratio [OR] 4·40, 95% CI 2·89–6·70, p<0·0001; and trial product estimand: 5·54, 3·54–8·68, p<0·0001). The odds of decreasing mean bodyweight from baseline to week 52 were higher with oral semaglutide than with sitagliptin (estimated mean change in bodyweight, treatment policy estimand: −2·6 kg [SE 0·3] vs −0·7 kg [SE 0·2], estimated treatment difference [ETD] −1·9 kg, 95% CI −2·6 to −1·2; p<0·0001; and trial product estimand: −2·9 kg [SE 0·3] vs −0·8 kg [SE 0·3], ETD −2·2 kg, −2·9 to −1·5; p<0·0001). Adverse events occurred in 197 (78%) of 253 participants in the oral semaglutide group versus 172 (69%) of 250 in the sitagliptin group, and nausea was the most common adverse event with oral semaglutide (53 [21%]). Two deaths occurred in the sitagliptin group during the trial. Interpretation: Oral semaglutide, with flexible dose adjustment, based on efficacy and tolerability, provided superior glycaemic control and weight loss compared with sitagliptin, and with a safety profile consistent with subcutaneous GLP-1 receptor agonists. Funding: Novo Nordisk A/S.